2017
DOI: 10.1038/s41598-017-01761-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical, and virologic features of two family clusters of avian influenza A (H7N9) virus infections in Southeast China

Abstract: This study aimed to investigate the epidemiological, clinical, and virologic characteristics of avian influenza A (H7N9) confirmed cases from two family clusters in Southeast China. Epidemiological data of the H7N9 confirmed cases and their close contacts were obtained through interviews and reviews of medical records. Of the four patients in these two family clusters, two cases had mild symptoms, one had severe symptoms, and one died. Three of the four patients had a history of exposure to live poultry or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In particular, limited human‐to‐human transmission of avian influenza A/H7N9 is supported by the small number of family and/or hospital clusters reported . Those patients with influenza‐like syndromes who come in close contact with poultry, confirmed patients or travel history in pandemic areas may be at high‐risk of H7N9 infection . Physicians working outside of China who see patients with influenza‐like illness should take a travel history.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, limited human‐to‐human transmission of avian influenza A/H7N9 is supported by the small number of family and/or hospital clusters reported . Those patients with influenza‐like syndromes who come in close contact with poultry, confirmed patients or travel history in pandemic areas may be at high‐risk of H7N9 infection . Physicians working outside of China who see patients with influenza‐like illness should take a travel history.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses were often carried out when human infections were identified, and genetically closely related H7N9 viruses were often isolated from chickens or environmental samples, mostly from the exposed live poultry markets (Shi et al 2013a). There were also several reports of clusters of human infection cases (Ding et al 2014;Xiao et al 2014;Mao et al 2015;Yi et al 2015;Xie et al 2017;Guo et al 2018;Wang et al 2018;Zhang et al 2019), although there remains no evidence of sustained human-to-human transmission (Hu et al 2014;Dong et al 2017;Liu et al 2017;Wang et al 2019).…”
Section: Emergence and Genetic Evolutionmentioning
confidence: 99%
“…We also uncovered additional mutations including D30 and A215 (Fan et al, 2009) in M1 protein, S42 in NS1 (Jiao et al, 2008), and V89 in PB2 (Xie et al, 2017), all of which indicated an enhanced virus adaption to mammalian host. Like those influenza A(H7N9) virus strains studied in previous epidemic seasons, all the three isolates harbored the mutations at N31 in M2 protein, but no substitution at the R292K in NA, indicating that the viruses could be amantadine resistant, but oseltamivir sensitive (Yen et al, 2013;Takeda et al, 2002).…”
Section: Discussionmentioning
confidence: 92%